Initial-boundary value problem for doubly nonlinear integro-differential equations with variable exponents of nonlinearity - Buhrii О.М. (Reports of the National Academy of Sciences of Ukraine, 2017)
We consider the initial-boundary value problem for doubly nonlinear parabolic equations with variable exponents of nonlinearity perturbed by a generator of the jump process arising from the theory of European options. The existence theorem for the problem is proved.